ANALYSIS OF PARENTS' RESPONSES TO YOUNG MARRIAGE IN TEENAGERS IN KUTAWARGI VILLAGE IN 2022 - Lisnawati Lisnawati; Nanik Yuliwati (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: The prevalence of early marriage in Indonesia in 2018 showed a high rate of 67% and there was an increase of 6% during 2019-2020. The incidence of early marriage in the village of Kutawargi Karawang in 2020 (32%) is higher than the previous year. Purpose: the research aims to find out how the Analysis of Parents' Responses to Young Marriage in Adolescents in Kutawargi Village in 2022. This research method uses quantitative analytical research. With a cross sectional study approach with a population of 34 people and a sample of 25 respondents selected by accidental sampling. Data was taken using a questionnaire which was then processed using a statistical program. Results: Based on education, there were 14 (56.0%) respondents with the highest education. Based on the mindset, there were 15 (60.0%) respondents with bad mindsets and there were 14 (56.0%) respondents with less economic status, there were 16 (64.0%) respondents who said marrying off children was not because of promiscuity, as well as the frequency of young marriages, there were 15 ( 60.0%) of respondents who married their children at a young age. The results of the statistical analysis found that teenagers in Kutawargi village marry young, namely education (ρ value = 0.000), parents' mindset (ρ value = 0.000), parents' economy (ρ value = 0.000), promiscuity (ρ value = 0.002) Conclusion: Analysis of parents' responses to young marriage among adolescents in Kutawargi village in 2022, namely educational factors, parents' mindset, parents' economy, and promiscuity. Therefore, parents are expected to have good relationships and communication with teenagers. Parents must also provide understanding and direction regarding marriage and the impact of teenage marriage. In addition, parents must also be able to control the association of teenagers so they do not fall into promiscuity.